2003
DOI: 10.1177/000331970305400605
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass in Dippers and Nondippers with Newly Diagnosed Hypertension

Abstract: Hypertensive subjects can be subdivided into 2 groups, dippers and nondippers, according to the presence or the lack of a nocturnal fall of blood pressure of more than 10%. Several studies have investigated cardiac organ damage in the 2 groups with discordant results, but they included subjects with different onset, severity, and treatment of hypertension. The authors selected 23 dippers and 17 nondippers affected by newly (< 1 year) diagnosed grades 1 and 2 hypertension, never treated, who underwent 24-hour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Many researchers have evaluated cardiac damage in untreated individuals with essential hypertension and found no significant differences between dippers and nondippers with respect to LV diameter (14,21), LV systolic and diastolic function (21), interventricular septum thickness, posterior wall thickness, relative wall thickness (14,45,56), LV concentric remodelling (45,56), LVH, LVM and LVMI (14,21,45,56), aortic distensibility (21) and atrial dimensions (56). However, in these studies, the classification of dipping status was based on a single ABPM session.…”
Section: Cardiac Geometrymentioning
confidence: 99%
“…Many researchers have evaluated cardiac damage in untreated individuals with essential hypertension and found no significant differences between dippers and nondippers with respect to LV diameter (14,21), LV systolic and diastolic function (21), interventricular septum thickness, posterior wall thickness, relative wall thickness (14,45,56), LV concentric remodelling (45,56), LVH, LVM and LVMI (14,21,45,56), aortic distensibility (21) and atrial dimensions (56). However, in these studies, the classification of dipping status was based on a single ABPM session.…”
Section: Cardiac Geometrymentioning
confidence: 99%
“…A number of studies have shown that individuals with essential hypertension and a nondipper BP pattern show an increased frequency of target organ damage. In particular, there is some evidence to suggest that they are at increased risk of LVH, left ventricular mass, left ventricular mass index, carotid artery intima to medial thickness, carotid artery plaques, silent cerebral infarct, stroke, cognitive impairment, microalbuminuria, and retinopathy [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of establishing a nondipper BP pattern lies in its proven association with more severe hypertensive target organ damage and its improved prediction of an increased cardiovascular (CV) risk, not only in hypertensives, but also in normotensives [4][5][6]. Left ventricular hypertrophy (LVH), carotid intima-media thickening, microalbuminuria and cerebrovascular diseases are much more prevalent in nondippers than in dippers [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With the use of the 24-hour ABPM, researchers have observed that BP usually fluctuates in a diurnal manner [3]. Diurnal refers to the daily variation of BP that is generally higher during the day than at night.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have failed to discover significant differences in cardiac and extra cardiac damage between night-time BP patterns among persons with essential hypertension. Several researchers have observed no significant differences in left ventricular hypertrophy (LVH) [10,11], left ventricular mass (LVM) [3,12], left ventricular mass index (LVMI) [3,13], carotid artery intimae to medial thickness [14,15], carotid artery plaques [15], cognitive functioning [16], microalbuminuria [17], and retinopathy [17].…”
Section: Introductionmentioning
confidence: 99%